Assimilation paths of immigrant children: Asian Indians and Filipinos compared. (September 2015) - Qian, Zhenchao; Shah, Priyank
Modes of accommodation and adaptation may influence minority immigrants' assimilation outcomes. Using census data from 1980, 1990, and 2000, we follow the Asian Indians and Filipinos who were 0–19 years old in 1980 and immigrated to the US in the 1970s. We apply cohort analysis to compare their educational attainment when they became 20–39 years old in 2000 with that of their parents in 1980 and 1990. Educational attainment, on average, was lower among Filipino immigrant children than among their parents but higher among Asian Indian immigrant children than among their parents. We then explore differences in educational attainment and intermarriage patterns between Asian Indians and Filipinos. Asian Indians were much more likely to complete college, but far less likely to marry whites than Filipinos. These findings offer the basis for the discussion of different paths of assimilation among middle-class immigrants.